Navigating Idealism and Societal Expectations: A Genetic Structuralist Analysis of Dewi Lestari’s Perahu Kertas - Derliana Hasibuan; Burhanuddin Arafah (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study aims to explore the author's worldview in Perahu Kertas, a novel by Dewi Lestari, using a qualitative approach within the framework of genetic structuralism. The analysis focuses on three main aspects: (1) the socio-cultural conditions depicted in the novel, particularly the characters’ interactions with their social environment; (2) societal perspectives on work, social status, and the conflict between parental expectations and individual aspirations; and (3) the author’s worldview, which highlights the struggles of young graduates navigating between securing a stable job for survival and pursuing their dreams for the sake of idealism. The findings demonstrate that the novel reflects the realities of Indonesian society, particularly the challenges faced by young individuals as they balance their ambitions with external pressures.